2022
DOI: 10.1007/s10212-021-00589-3
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Composition of Collaborative Groups’ Emotion Regulation in Negative Socio-emotional Interactions

Abstract: Research indicates that to adjust a group’s emotional atmosphere for successful collaborative learning, group members need to engage in group-level emotion regulation. However, less is known about the whys and ways regulation is activated at a group level. This research explores what triggers 12-year-old primary school students’ (N = 37) negative socio-emotional interactions during a collaborative science task and whether the nature of the trigger makes a difference to group-level emotion regulation strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This could be done for example by different types of awareness tools (Järvelä, Kirschner, et al, 2016; Kwon, 2020; Lavoué et al, 2020). Furthermore, the groups could benefit from more knowledge and support on how to apply appropriate regulation strategies to overcome the socio‐emotional challenges (for emotion regulation strategies, see e.g., Bakhtiar et al, 2018; Järvenoja et al, 2019; Mänty et al, 2022). However, the challenge for both teachers and students is to recognize these socio‐emotionally critical episodes in situ and to provide learning groups with timely information and support.…”
Section: Discussionmentioning
confidence: 99%
“…This could be done for example by different types of awareness tools (Järvelä, Kirschner, et al, 2016; Kwon, 2020; Lavoué et al, 2020). Furthermore, the groups could benefit from more knowledge and support on how to apply appropriate regulation strategies to overcome the socio‐emotional challenges (for emotion regulation strategies, see e.g., Bakhtiar et al, 2018; Järvenoja et al, 2019; Mänty et al, 2022). However, the challenge for both teachers and students is to recognize these socio‐emotionally critical episodes in situ and to provide learning groups with timely information and support.…”
Section: Discussionmentioning
confidence: 99%
“…Educational organisations could use the results in developing activities promoting student well-being. Emotions play a role in learning (Artino, 2012;Mänty et al, 2023), for instance, negative emotions cause challenges in learning and competence development influencing even graduation. Higher education institutions should take students' needs into account when designing student-centred solutions, distance or blended learning.…”
Section: Discussionmentioning
confidence: 99%
“…Individual ER in academic contexts emerges when students attempt to monitor, assess, and adjust their own emotions, including the type, intensity, and duration of the given emotion, in order to complete their academic tasks (Boekaerts & Pekrun, 2015). While individual ER in academic contexts is focused on personal adjustments, in collaborative contexts, it becomes a social process (Mänty et al, 2023), so it is likely that the individual ER strategies differ from those utilized in group contexts. Importantly, the findings of the current study suggest similarities between students’ self-reported emotion-regulation strategies at the individual level and to those observed at group level in authentic learning contexts (e.g., Järvenoja & Järvelä, 2013; Lobczowski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%